Rancang Bangun Kolam Lele dengan Teknologi Bioflok dan Energi Terbarukan - Luh Putri Adnyani (Universitas Lambung Mangkurat, 2026)
Catfish farming is one of the freshwater fisheries businesses that is widely developed by the community because it has high economic value, easy farming techniques, and relatively low business capital. However, in Kampung Pelita RT 10, Sumber Rejo Village, Balikpapan Tengah District, catfish farming activities that were previously running are no longer active due to limited facilities, conventional methods, and high operational costs. Through this community service activity, a biofloc method was implemented in combination with renewable energy (solar panels) to support the pond aeration system. The activity was carried out over three months through the stages of survey, problem identification, design, implementation, and evaluation. The results of the activity showed that the biofloc system was able to increase feed efficiency by up to 25% and maintain stable water quality, while the use of solar panels succeeded in reducing electricity costs and ensuring a 24-hour oxygen supply. Based on a questionnaire of 20 respondents, 80% of residents showed an increase in their understanding of biofloc and solar energy technologies. Thus, the application of this appropriate technology not only increases the productivity and efficiency of aquaculture but also strengthens community independence in managing an environmentally friendly energy-based economy.